Perfil epidemiológico e espacial da hanseníase em menores de 15 anos de idade, na região metropolitana de Belém, estado do Pará - OLIVEIRA, Silvio Silva (Universidade Federal do Pará, 2019)
Leprosy is an infectious, curable disease, however, with great potential for generating physical incapacity. Knowing the impact of leprosy in children under 15 allows estimating the level of transmission, the intensity of the endemic disease and evaluating the effectiveness of health services in combating this disease, which is more prevalent in poor populations and represents a growing health problem in the this study analyzed the epidemiological profile of leprosy in children under 15 years of age and the population coverage of the Family Health Strategy in the Metropolitan Region of Belém, state of Pará, from 2006 to 2015. Quantitative study with an ecological study design in a historical series of leprosy cases reported in the years 2006 to 2015, using secondary data from the Ministry of Health's Notifiable Diseases and Basic Attention Database State of Pará, Brazil. Of the 675 cases, the majority (58.96%) were detected by referral, predominantly male (55.70%), black + brown (81.63%) and incomplete elementary school (77.48 %). The most frequent age group (65.09%) was children aged 10 to 14 years, with a predominance of paucibacillary forms and a higher frequency of dimorphic clinical form. The evolution of the standardized rate of detection of leprosy in less than 15 years, presented geographically, showed a high level of hyperendemicity in the municipalities of Castanhal, which had population coverage of the Consolidated Family Health Strategy and Marituba with intermediate coverage. It was presented with hyperendemicity in the municipality of Santa Bárbara do Pará also as a consolidated coverage and very high endemicity in the municipalities of Ananindeua with intermediate coverage, Belém with incipient coverage, Benevides and Santa Izabel do Pará with consolidated coverage. The areas of spatial autocorrelation for the transmission of the disease appeared to form two clusters, the first one involving the municipalities of Ananindeua, Belém and Benevides and the second one formed by the municipality of Castanhal located opposite to the first one. The highest densities of mean detection rates were observed in the municipalities of Marituba that spread to the municipalities of Ananindeua and Benevides and also in the municipality of Castanhal, representing to some extent the areas of greatest risk for the transmission of the disease. In the city of Belém, the capital of the State of Pará, the population coverage of the Family Health Strategy was incipient in most of the neighborhoods, although in some of the Mosqueiro Island it was consolidated, contradictorily putting those areas with the highest densities of average detection rates. The magnitude of the endemic disease, the strength of the morbidity and the tendency of the disease, indicated by the indicators of epidemiological follow-up remained high and the coverage of the Family Health Strategy, although consolidated in most municipalities, was not homogeneously distributed to guarantee universal coverage to the territories , implying in some way with this epidemiological situation, to affirm that leprosy is a serious public health problem in the Metropolitan Region of Belem.